ANALISIS TINGKAT KEPUASAN DAN PENERIMAAN MAHASISWA TERHADAP SIDIA DENGAN MENGGUNAKAN METODE EUCS DAN TAM - Sa'diyah, Lailatul Mukharromatus; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
In the current era of globalization, technological developments in the world of education have created various new features that can help in the teaching and learning process. One implementation is E-learning, which enables the online learning process. Surabaya State University (UNESA) implemented E-Learning specifically for students in 2015 to facilitate teaching and learning activities to be more flexible because the material in UNESA E-Learning can be accessed anytime and anywhere, is easy to understand, saves energy, costs and time. Since 2023, the UNESA Single Sign On (SSO UNESA) Dashboard has changed its appearance and tools. One of the SSO facilities that has undergone changes is UNESA E-learning. Therefore, this research aims to conduct a comprehensive analysis of the level of student acceptance and satisfaction with the use of SIDIA. This analysis will be carried out using the End User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) methods. The data collection process was carried out by distributing questionnaires to 100 respondents. Based on the results of the analysis carried out using the EUCS method, the results obtained were that all hypotheses were accepted, namely Content had an effect on user satisfaction, Accuracy had an effect on user satisfication, Timeliness had an effect on user satisfication, Format had an effect on user satisfication, and Ease of Use had an effect on user satisfication . This shows that users are satisfied with SIDIA. Meanwhile, for the TAM method, the results also showed that all hypotheses were accepted, namely Perceived Ease of Use (PEOU) had an effect on Acceptance of IT, and Perceived Ease of Use (PEOU) had an effect on Acceptance of IT. This shows that the user accepts the use of the SIDIA system. Keywords: E-Learning, SIDIA, Satisfaction, Acceptance, Users, EUCS (End user Computing Satisfaction), TAM (Technology Acceptance Model).